EXPERIENCE OF THE UNITED STATES OF AMERICA AND THE REPUBLIC OF CHINA IN DEVELOPING CLUSTERS IN UZBEKISTAN - Khudaykulov Sirojiddin Uzok ugli (Journals Park Publishing, 2025)
This article examines the role of clusters in the economy of the USA and China, their types and varieties of products they produce. Opinions of leading research scientists about clusters. The procedure for organizing agricultural clusters. The results of implementing the cluster system in several areas in leading countries are covered in detail.
Keywords: Clusters, tax administration, volume of turnover, working staff, tax revenues, agro-industrial, buttermilk-agricultural clusters, tourism, agriculture, automotive, industry.